Type I Interferonopathy among Non-Elderly Female Patients with Post-Acute Sequelae of COVID-19 - Donghua Xu; Xuebin Qin (Viruses, 2024)
The pathophysiological mechanisms of the post-acute sequelae of COVID-19 (PASC) remain unclear. Sex differences not only exist in the disease severity of acute SARS-CoV-2 infection but also in the risk of suffering from PASC. Women have a higher risk of suffering from PASC and a longer time to resolution than men. To explore the possible immune mechanisms of PASC among non-elderly females, we mined single-cell transcriptome data from peripheral blood samples of non-elderly female patients with PASC and acute SARS-CoV-2 infection, together with age- and gender-matched non-PASC and healthy controls available from the Gene Expression Omnibus database. By comparing the differences, we found that a CD14+ monocyte subset characterized by higher expression of signal transducers and activators of transcription 2 (STAT2) (CD14+STAT2high) was notably increased in the PASC patients compared with the non-PASC individuals. The transcriptional factor (TF) activity analysis revealed that STAT2 and IRF9 were the key TFs determining the function of CD14+STAT2high monocytes. STAT2 and IRF9 are TFs exclusively involving type I and III interferon (IFN) signaling pathways, resulting in uncontrolled IFN-I signaling activation and type I interferonopathy. Furthermore, increased expression of common interferon-stimulated genes (ISGs) has also been identified in most monocyte subsets among the non-elderly female PASC patients, including IFI6, IFITM3, IFI44L, IFI44, EPSTI1, ISG15, and MX1. This study reveals a featured CD14+STAT2high monocyte associated with uncontrolled IFN-I signaling activation, which is indicative of a possible type I interferonopathy in the non-elderly female patients with PASC.